Evaluation of the green economic value added index in the game of enterprise capital providers - Wunhong Su; Quansheng Zhang; Yunxia Ling; Wong Ming Wong (Heliyon, 2024)
This study explores the performance evaluation of steel enterprises, emphasizing the importance of green environmental performance. Based on the review of the current situation of green investment research, economic added value evaluation system, and game analysis of enterprise capital providers, this study discusses the comprehensive evaluation of games among enterprise capital providers from the perspective of green economic added value. It constructs a game model of capital providers from the perspective of green investment. This model is based on the probability of creditors making green bond investments and shareholders pledging equity, deriving game results, and using economic added value returns to measure enterprise performance. The main data in this study are from the CSMAR database, a corporate governance project, and the relevant environmental protection data from Nangang's annual report. The results show that the green economic added value return rate is higher than the traditional economic added value return rate, indicating that environmental investments do not reduce the operational performance of enterprises. The game of capital providers leans towards equity investment and does not enhance enterprise performance at the expense of the environment. The green economic added value index only reflects past operational performance, based on which enterprises can design reasonable performance evaluation mechanisms, encouraging capital providers to favor environmental investments. This study has important theoretical and practical significance, guiding enterprises' strategic choices during green transformation.